Structural panel Bayesian VAR with multivariate time-varying volatility to jointly deal with structural changes, policy regime shifts, and endogeneity issues - Antonio Pacifico (Econometrics, 2021)
This paper improves a standard Structural Panel Bayesian Vector Autoregression model in order to jointly deal with issues of endogeneity, because of omitted factors and unobserved heterogeneity, and volatility, because of policy regime shifts and structural changes. Bayesian methods are used to select the best model solution for examining if international spillovers come from multivariate volatility, time variation, or contemporaneous relationship. An empirical application among Central-Eastern and Western Europe economies is conducted to describe the performance of the methodology, with particular emphasis on the Great Recession and post-crisis periods. A simulated example is also addressed to highlight the performance of the estimating procedure. Findings from evidence-based forecasting are also addressed to evaluate the impact of an ongoing pandemic crisis on the global economy.
Keywords: A1; C01; E02; H3; N01; O4; 330; Bayesian methods; Central-Eastern and Western Europe; change-points; endogeneity issues; multivariate time-varying volatility; structural panel VAR